Peningkatan Kapasitas Petugas Bea Cukai Belawan melalui Pelatihan Adobe Illustrator untuk Mendukung Visualisasi Data dan Publikasi - Siahaan, Andysah Putera Utama; Kariyani (LKP KARYA PRIMA KURSUS, 2024)
This community service project aimed to provide graphic design training using Adobe Illustrator software to staff at the Belawan Customs Office. The training, conducted over 7 days in December 2016, sought to enhance the staff's ability to present information visually through more engaging, effective, and professional media. The training was implemented using a hands-on approach, where participants practiced using Adobe Illustrator directly, starting from basic features to more advanced design techniques, such as creating infographics and posters. The training materials were tailored to the specific needs of Customs officers to support socialization activities and visual reporting. Additionally, intensive mentorship ensured that each participant could effectively grasp the material. The results of this community service showed a significant improvement in participants' skills. They were able to produce graphic designs relevant to their duties, increasing efficiency and independence in creating visual materials. This project also had a positive impact on participants' understanding of the importance of graphic design in supporting the operational performance of the Customs Office. Through this training, it is expected that Belawan Customs Office staff will be more self-reliant and creative in producing visual content, thereby improving the effectiveness of information communication to the public and other stakeholders.